Population prevalence of individuals meeting criteria for hereditary breast and ovarian cancer testing. (18th September 2019) - Greenberg, Samantha; Buys, Saundra S.; Edwards, Sandra L.; Espinel, Whitney; Fraser, Alison; Gammon, Amanda; Hafen, Brent; Herget, Kimberly A.; Kohlmann, Wendy; Roundy, Camille; Sweeney, Carol
Abstract: Background: Personal cancer diagnosis and family cancer history factor into which individuals should undergo genetic testing for hereditary breast and ovarian cancer (HBOC) syndrome. Family history is often determined in the research setting through kindreds with disease clusters, or clinically from self‐report. The population prevalence of individuals with diagnostic characteristics and/or family cancer history meeting criteria for HBOC testing is unknown. Methods: Utilizing Surveillance, Epidemiology, and End Results (SEER) cancer registry data and a research resource linking registry records to genealogies, the Utah Population Database, the population‐based prevalence of diagnostic and family history characteristics meeting National Comprehensive Cancer Network (NCCN) criteria for HBOC testing was objectively assessed. Results: Among Utah residents with an incident breast cancer diagnosis 2010‐2015 and evaluable for family history, 21.6% met criteria for testing based on diagnostic characteristics, but the proportion increased to 62.9% when family history was evaluated. The proportion of cases meeting testing criteria at diagnosis was 94% for ovarian cancer, 23% for prostate cancer, and 51.1% for pancreatic cancer. Among an unaffected Utah population of approximately 1.7 million evaluable for family history, 197, 601 or 11.6% met testing criteria based on family history. Conclusions: This study quantifies the population‐based prevalence of HBOC criteria using objectively determined genealogy and cancer incidence data. Sporadic breast cancer likely represents a portion of the high prevalence of family cancer history seen in this study. These results underline the importance of establishing presence of a deleterious mutation in an affected family member, per NCCN guidelines, before testing unaffected relatives. Abstract : Using diagnostic and family history data, almost 63% of individuals with breast cancer diagnoses meet criteria for genetic testing based on diagnostic and family history. Utilizing the Utah Population Database, a research resource that links of four decades of cancer registry records to genealogies, almost 12% of the unaffected Utah population meets criteria for genetic testing. Given the high proportion of the population, targeting affected cases can maximize family impact while minimizing cost.